2021
DOI: 10.1002/iid3.409
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and prognostic value of soluble VCAM‐1 in ST‐segment elevation myocardial infarction patients

Abstract: Background Soluble vascular cell adhesion molecule‐1 (sVCAM‐1) is a biomarker of endothelial activation and inflammation. There is still controversy as to whether it can predict clinical outcome after ST‐elevation myocardial infarction (STEMI). Our aim was to assess the sVCAM‐1 kinetics and to evaluate its prognostic predictive value. Method We prospectively enrolled 251 consecutive STEMI patients who underwent coronary revascularization in our university hospital. Blood samples were collected at admission, 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…For example, one previous study indicates that the elevation of IL‐6 is correlated with high MACE risk in STEMI patients who undergo PCI therapy 13 . Another study finds the important role of VCAM‐1 in the occurrence of post‐PCI restenosis 23 . Nevertheless, the prognostic value of inflammatory cytokines lacks comprehensive study at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one previous study indicates that the elevation of IL‐6 is correlated with high MACE risk in STEMI patients who undergo PCI therapy 13 . Another study finds the important role of VCAM‐1 in the occurrence of post‐PCI restenosis 23 . Nevertheless, the prognostic value of inflammatory cytokines lacks comprehensive study at present.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have been carried out to explore the correlation of some specific inflammatory cytokines with MACE risk in STEMI patients. 13 , 15 , 23 , 24 , 25 For example, one previous study indicates that the elevation of IL‐6 is correlated with high MACE risk in STEMI patients who undergo PCI therapy. 13 Another study finds the important role of VCAM‐1 in the occurrence of post‐PCI restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating endothelial cells in the peripheral blood as well as E-selectin, von Willebrand factor and soluble thrombomodulin were shown to be significantly higher in patients with HF although they did not present significant differences between AHF and chronic HF and did not correlate with P-BNP ( Chong et al, 2006a ), ejection fraction or New York Heart Association (NYHA) class ( Chong et al, 2006b ). Also, VCAM-1 and ICAM-1 were shown to be associated with the development of new post-acute myocardial infarction HF symptoms ( Lino et al, 2019 ) and increased subset-specific monocyte expression of their receptors were observed in AHF patients, with potential prognostic value of VCAM-1R ( Wrigley et al, 2013 ) and sVCAM-1 after ST-elevation myocardial infarction ( Hayek et al, 2021 ). But of all these, serum endocan has been one of the most qualified for the cardiovascular arena ( Bessa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMRSegTools, includes customised tools for user-assisted myocardial segmentation; manual, semi-and automatic lesion segmentation which can be used in the generation of training data sets for Machine Learning (ML) strategies. This computer-based tool can be easily deployed on clinical infrastructures, closing the gap between analysis methods and their direct utilisation in clinical trials, as demonstrated in the studies [22][23][24][25].…”
Section: Plos Onementioning
confidence: 99%
“…A comparison between expert and automated segmentation methods is presented in Figs 7 and 8 as an example of the output of the current version. CMRSegTools has been tested and used successfully in several studies [22][23][24][25].…”
Section: Plos Onementioning
confidence: 99%